KEPEMIMPINAN KHALIFAH ABU BAKAR AL-SHIDDIQ - Muhammad Rahmatullah (Khatulistiwa, 2014)
History of the leadership at the time of the Caliph Abu Bakr Al-Shiddiq has a very important meaning in the history of the Islamic Ummat. The reasons for this, among them are: first, the leadership or the Caliph at that time could not be separated from power and if it was not in accordance with the wishes of the people, then it might have caused a conflict; second, a leader is not just a matter of like or dislike, but many factors play an important role such the viewpoint or approach that is used, whether it is his personality, skills, talent, characters or authority he has; third, regardless of the differences of opinion about who is entitled to occupy the office of the Caliphate, which history has proven clearly that Abu Bakr became the First democratically elected Caliph in the history of Islam. The "Riddah" war was as evidence of the accomplishment of Caliph Abu Bakr Al-Shiddiq, by displaying two prominent characters i.e. his gentleness that he showed to the Muslims who committed sin, and his firmness in dealing with Muslims who rebelled. Not only did he manage to uphold the Government of Medina that was on the brink of collapse and reunite the divided tribes, but he also managed to Islamize the tribes that were previously hostile to Islam.